Z-Source Inverter Design Analysis & Simulation using Maximum Boost Methods - Manoj Kumar Prajapati (Journal of Electronic Design Engineering, 2020)
The Z-source converter (ZSC) is a power conversion topology it changes one form of energy to another form of energy. ZSI inverter has a specialty of buck and boost of the DC input supply. It uses passive elements for buck and boost. This thesis presents the study and design of an impedance network that is used in a power conversion system. The impedance network is made of LC components and this impedance network is a coupling between the power source and converter circuit. In the thesis, we have discussed the PWM scheme and its uses for switching in the ZSI circuit. We have also analyzed a maximum boost control scheme to boosting up an input DC supply because of the change value of the modulation index. We have examined and reduced the complete harmonic distortion in the ZSI circuit. The Maximum Boost control scheme of ZSI is analyzed using simulation with MATLAB/Simulink.